2012
DOI: 10.5539/gjhs.v5n2p134
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Burden of Diseases in a Rapidly Developing Economy: State of Qatar

Abstract: Background:The Global Burden of Disease (GBD) study has provided a conceptual and methodological framework to quantify and compare the health of populations.Aim:The objective of the study was to assess the national burden of disease in the population of Qatar using the disability-adjusted life year (DALYs) as a measure of disability.Methods:We adapted the methodology described by the World Health Organization for conducting burden of disease to calculate years of life lost due to premature mortality (YLL), yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…Moreover, the annual incidence of burn-related mortalities exceeds 300,000 worldwide [2]. A recent report from Qatar showed that the burden of diseases among men was found three times more than of women's [3]. For men, chronic diseases like CVD (15.7%) and motor vehicle crashes (MVCs) (13.7%) represent a great burden and an important source of lost years of healthy life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the annual incidence of burn-related mortalities exceeds 300,000 worldwide [2]. A recent report from Qatar showed that the burden of diseases among men was found three times more than of women's [3]. For men, chronic diseases like CVD (15.7%) and motor vehicle crashes (MVCs) (13.7%) represent a great burden and an important source of lost years of healthy life.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, there is a lack of relevant literature on the incidence of trauma involving female gender. We reviewed all the relevant studies from our institute during the last 5 years period (Table  1) [3,7-18]. In these studies, representation of females was very low in comparison to males.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer forms one of the leading causes of millions of deaths worldwide. An increasing incidence in the prevalence of this fatal disease is being observed in the Middle East region, with the breast cancer (Al-Kuraya et al, 2005) and colon cancer (Arafa and Farhat, 2015) ranking high, especially within the State of Qatar (Rasul et al, 2001;Bener et al, 2008;Bener et al, 2010;Bener et al, 2012). Among Arab women, breast cancer is ranked first among all cancers and has the highest rate of morbidity and mortality among women (Bazarbashi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts were made to develop road safety strategies for developing countries such as those for Jordan, Saudi Arabia, Qatar and Bahrain [20]- [22]. However, some of these attempts were not very comprehensive and many were not fully implemented.…”
Section: Strategies and Action Plans For Road Safety Improvementmentioning
confidence: 99%